Manufacturing of MOL and Amfoter Feed Palm Leaves and Fronds on Breeders in Talun Kenas Village, STM Hilir District - Br. Ketaren, Nurjama'yah; Yunilas; Siregar, Etti Sartina (Talenta Publisher, 2023)
Breeders experience difficulties in providing grass as animal feed due to the narrowness of grazing land and changes in the function of land where agricultural land has become oil palm plantations. Farmers only expect the grass that is under the oil palm plants. Farmers have difficulty getting grass for their livestock when there is less grass under the palm trees, especially during the dry season. It is necessary to transfer the technology of utilizing palm leaves and fronds as quality and continuously available sheep feed. This can be overcome by applying the manufacture of MOL and Amphoteric feed from palm leaves and fronds. The method applied to this service activity is the transfer of knowledge in the form of socialization activities in the form of: 1) Introduction to types of plantation and agro-industrial waste that can be used as alternative forages and concentrates, (2) Formulation of sheep feed, (3) Manufacturing technology MOL, (4) manufacture of amphoteric feed, and 5) Monitoring and assistance. Socialization is done by training and lecture methods. The lecture activity was finished, followed by a question and answer session between the participants and the speakers. The results of the farmer's activities found out how to make MOL from palm leaves and fronds which are used to manufacture amphoteric feed. The knowledge and skills possessed by these breeders are expected to overcome the difficulties of breeders in providing grass, as well as to increase the productivity of sheep.